2021
DOI: 10.3390/life11111247
|View full text |Cite
|
Sign up to set email alerts
|

Role of PTEN, PI3K, and mTOR in Triple-Negative Breast Cancer

Abstract: Breast cancer is the most commonly occurring malignancy and the leading cause of cancer-related death in women. Triple-negative breast cancer (TNBC) is the most aggressive subtype and is associated with high recurrence rates, high incidence of distant metastases, and poor overall survival. The aim of this study was to investigate the PI3K/PTEN/Akt/mTOR pathway as one of the most frequently deregulated pathways in cancer. We aimed to explore the impact of PI3K and mTOR oncogenes as well as the PTEN tumor suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…PTEN acts as a checkpoint for PI3K, which enhances the PI3K/AKT survival pathway. PTEN deficiency and high PI3K and mTOR expression are linked to a poor prognosis in triple negative breast cancer patients 60 . In our study the loss of PTEN immunoreactivity and upregulation of PI3K were noted in cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN acts as a checkpoint for PI3K, which enhances the PI3K/AKT survival pathway. PTEN deficiency and high PI3K and mTOR expression are linked to a poor prognosis in triple negative breast cancer patients 60 . In our study the loss of PTEN immunoreactivity and upregulation of PI3K were noted in cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K is highly expressed in 40% of TNBC, and its expression is marginally higher in TNBC than in hormone receptor-expressing (HR+) breast cancer [ 37 ]. A high expression of PI3K is correlated with a larger tumor size, lymph node metastases, advanced tumor stage in TNBC [ 37 ], and unfavorable outcomes in various solid tumors [ 38 , 39 , 40 , 41 ]. The PI3K/mTOR pathway is also strongly activated in IBC tumors [ 42 ], and the PI3K/Akt and PI3K/mTOR pathways are crucial for IBC invasion [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is a key integrator of signals that control protein and lipid biosynthesis and growth factor–driven cell cycle progression [ 57 ]. mTOR was highly expressed in 44% of TNBC, and the high expression of mTOR was correlated with a high pathological prognostic TNBC stage [ 37 ]. Expression levels of mTOR were significantly higher in TNBC than in HR+ tumors, and high mTOR expression was associated with advanced tumor stage [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The homologous tumor suppressor of phosphatase and tensin (PTEN) downregulation is common in TNBC. Accordingly, previous investigations have reported a relationship between PTEN expression and the EMT process [ 10 , 11 , 12 , 13 ]. In contrast, some studies have suggested that, in different cancer types, early growth response 2 (EGR2) expression is correlated with apoptosis promotion, with the ETM process inhibitor playing a role in this correlation.…”
Section: Introductionmentioning
confidence: 99%